PSV-11 Grazing diverse combination of tanniferous and non-tanniferous legumes: Implications for foraging behavior, performance and hair cortisol in beef cattle. (30th November 2020) - Lagrange, Sebastian; MacAdam, Jennifer; Villalba, Juan J
Abstract: We tested the effect of increasingly diverse combinations of tanniferous legumes (birdsfoot trefoil-BFT, sainfoin-SF) and alfalfa (ALF) on cattle foraging behavior, performance and hair cortisol concentration. Pairs of heifers (401 ± 49.6 kg) grazed three spatial replications of seven treatments (n = 3/treatment): monocultures (BFT, SF, ALF) and all possible 2- and 3-way choices among strips of these legumes in a completely randomized block design in two 25-d periods during 2 consecutive years. The fewest grazing events occurred in BFT (42.0% of the total scans recorded; P < 0.10), with other treatments ranging between 47.8 (SF-BFT) and 52.6% (ALF-SF) of the total scans recorded. Heifers selected a varied diet, preferring SF over BFT or ALF in 46:27:27 and 70:30 ratios (3- and 2-way choice, respectively) and preferred BFT over ALF (62:38 ratio). All treatments followed similar daily grazing patterns (P >0.10), with two major grazing events (1 hour after sunrise and 3 hours before sunset). No differences among treatments were observed for the number of steps taken, motion index, or percentage of time spent standing (1, 600, 5, 356, and 45.3%, respectively; P >0.10), suggesting that heifers in choice treatments did not invest extra time in walking, searching or patch-switching activities relative to monoculture treatments. Heifers in the 3-way choice gained more BW (1.27 Kg/d) than in monocultures (1.00 kg/d; P = 0.014), or 2-way choices (0.97 kg/d; P = 0.007), suggesting nutritional synergism among legumes in the treatment of greatest diversity. No differences in hair cortisol concentration were observed among treatments, with values ranging between 1.40 (BFT) and 2.12 ng/g (3-way choice) (P >0.10). Thus, forage diversity enhanced animal performance, likely driven by interactions among condensed tannins and dietary protein, without affecting hair cortisol levels or grazing efficiency, explained by the spatial arrangement (strips) of the forage species presented.